The prevalence of PTSD and major depression in the global population of adult war survivors: a meta-analytically informed estimate in absolute numbers. Issue 1 (1st January 2019) - Hoppen, Thole Hilko; Morina, Nexhmedin
ABSTRACT: Background : Elevated prevalences of post-traumatic stress disorder (PTSD) and major depression (MD) have been reported in populations exposed to war. However, no global estimates of war survivors suffering from PTSD and/or MD in absolute numbers have been reported. Objective : We made the first attempt to estimate in absolute numbers how many adult war survivors globally may suffer PTSD and/or MD, which should inform local and global mental health programmes. Method : Drawing on the Uppsala Conflict Database, we reviewed all countries that suffered at least one war within their own territory between 1989 and 2015 (time span chosen on availability of geo-referenced data and population estimates). We then conducted a meta-analysis of current randomized epidemiological surveys on prevalence of PTSD and/or MD among war survivors. Finally, we extrapolated our results from the meta-analysis on the global population of adult war survivors by means of using general population data from the United Nations. Results : We estimate that about 1.45 billion individuals worldwide have experienced war between 1989 and 2015 and were still alive in 2015, including one billion adults. On the basis of our meta-analysis, we estimate that about 354 million adult war survivors suffer from PTSD and/or MD. Of these, about 117 million suffer from comorbid PTSD and MD. Conclusions : Based on the slim available evidence base, the global number of adult war survivors suffering PTSD and/or MD is vast. Most war survivors live in low-to-middle income countries with limited means to handle the enormous mental health burden. Since representative high quality data is lacking from most of these countries, our results contain a large margin of uncertainty and should be interpreted with caution.